Nutritional value and application of dried distillery grains with solubles from different sources in rabbit feeding - Vázquez, Ysnagmy; Bernal, H.; Valdivié, M.; Gutiérrez, E.; Mora, L. M.; Hernández, C. A. (Cuban Journal of Agricultural Science, 2018)
The objective of this study was to gather information related to nutritional composition of dried distillery grains with solubles from different sources (maize, sorghum, wheat and barley), as well as to summarize research that has been conducted with the use ofthis by-product in rabbits. It is also reported about the advantages and limitations of dried distillery grains with solubles for this species, with the knowledge that it is possible that digestive specificities of rabbits make that some of the nutritional losses observed in other monogastric animals are not so relevant for rabbits. Dried distillery grains with solubles constitute a good protein source, digestible energy, neutral detergent fiber and phosphorus, which makes them a favorable food ingredient to be used in rabbit feeding.Key words: feeding, rabbits, dried distillery grains with solubles, inclusion levels, nutritional value